Once bitten, twice shy? Medically-attended injuries can sensitise parents to children's risk of injuries on playgrounds. Issue 1 (3rd February 2009) - Morrongiello, B A; Howard, A W; Rothman, L; Sandomierski, M
Abstract : Objective: To compare risk perceptions of parents whose child sustained a medically attended playground injury (cases) with those of parents whose child had not (controls) to address two questions. Does having a child experience a medically attended injury: (1) sensitise parents to children's injury vulnerability and severity; (2) influence parents' appraisal of the injury mechanism (child's behaviour), attributions for injuries or beliefs about strategies for prevention? Method: Each case–control parent dyad was assigned to one of two conditions: (1) being presented with 10 common injury-risk playground behaviours specific to the equipment on which their child had been hurt, and asked to appraise injury vulnerability and severity; or (2) being presented with scenarios about playground injuries that varied in severity but were all based on the same child behaviour, and asked questions about this behaviour, attributions for injury and strategies for prevention. Results: The results support the occurrence of a sensitisation process. Compared with control parents, case parents showed higher ratings of injury severity and children's vulnerability to injury, made fewer attributions for injuries to bad luck, and endorsed a greater diversity of prevention strategies, including parent (closer supervision), child (teaching rules about safe play on playgrounds) and environmental (modifications to playgrounds). Conclusions: A child's medically attended injury can create a "teachable moment" for the parent. Linking injury-prevention programming to this teachable moment may increase the likelihood of evoking changes in parental supervisory behaviour and their setting of rules limiting their child's risk behaviours to reduce the occurrence of childhood injury.